COMMON ERRORS IN PROPOSAL WRITING: A CROSS SECTIONAL STUDY AMONG POST GRADUATE MEDICAL TRAINEES AT PESHAWAR - Ali, Farhad; Rasool, Ghulam; Ullah, Kifayat; Khaliq, Abdul; Ullah, Irfan; Hassan, Sabreen; Ul Haq, Zia (Journal of Ayub Medical College Abbottabad, 2019)
Background: Proposal writing before starting research study is the key component of the any research project and quality of the research depends upon how the proposal was designed and planned. Objectives of this study was to determine the frequency of most common errors in proposal writing by post graduate medical residents of College of physician and surgery of Pakistan (CPSP) at Peshawar. Methods: A cross sectional study was carried at Khyber College of Dentistry (KCD) Peshawar from August 2017 to May 2018.We conducted the reviewed of Form S of 43 proposals through convenience sampling. Each Form S consist of 34 question. All the questions were dichotomous which were presented in the form of frequency and percentages. Data were analysed by SPSS-22. Result: Out of 43 proposal, the result shows that 53.5% (n=23) of the candidates have not explained the introduction in their own words while suitable statistical tests were not mentioned in more than half of the 67.4% (n=29) proposal. References were not written in Vancouver style 51.2% (n=22) as well as hypothesis was not applicable in 62.8% (n=27) of the studies. However only 39.5% (n=60.5) of the trainees phrased the hypothesis properly. Conclusion: Majority of the candidates were unable to write the proposal according to the recommended guidelines. Application of the appropriate statistical measures was found as a challenge for the candidates. Similarly, objectives were not clearly defined in terms of SMART concept. Keywords: Proposal Medical Writing; Postgraduate medical Trainee; CPSP; Medical education; Medical Errors